Thermal, mechanical, and morphological properties of oil palm cellulose nanofibril reinforced green epoxy nanocomposites - Yusuf, J.; Salit @ Sinon, Mohd Sapuan; Rashid, Umer; Ilyas, R.A.; Hassan, M.R. (Elsevier, 2024)
In this study, significant improvements in mechanical properties have been seen through the efficient inclusion of Oil Palm Cellulose Nanofibrils (CNF) as nano-fillers into green polymer matrices produced from biomass with a 28 % carbon content. The goal of the research was to make green epoxy nanocomposites utilizing solution blending process with acetone as the solvent with the different CNF loadings (0.1, 0.25, and 0.5 wt%). An ultrasonic bath was used in conjunction with mechanical stirring to guarantee that CNF was effectively dispersed throughout the green epoxy. The resultant nanocomposites underwent thorough evaluation, comparing them to unfilled green epoxy and evaluating their morphological, mechanical, and thermal behavior using a variety of instruments. Field-emission scanning electron microscopy (FE-SEM) was used to validate findings, which showed that the CNF were dispersed optimally inside the nanocomposites. The thermal degradation temperature (Td) of the nanocomposites showed a marginal decrement of 0.8 % in temperatures (from 348 °C to 345 °C), between unfilled green epoxy (neat) and 0.1 wt% of CNF loading. The mechanical test results, which showed a 13.3 % improvement in hardness and a 6.45 % rise in tensile strength when compared to unfilled green epoxy, were in line with previously published research. Overall, the outcomes showed that green nanocomposites have significantly improved in performance. © 2024 Elsevier B.V.